One pot oxidative dehydration - oxidation of polyhydroxyhexanal oxime to polyhydroxy oxohexanenitrile: A versatile methodology for the facile access of azasugar alkaloids. (29th November 2016) - Khobare, Sandip R.; Gajare, Vikas; Reddy, E. Vishnuvardhan; Datrika, Rajender; Banda, Malavika; Siddaiah, Vidavalur; Pachore, Sharad S.; Timanna, Upadhya; Dahanukar, Vilas H.; Syam Kumar, U.K.
Abstract: A unique oxidative dehydration-oxidation of polyhydroxy-oxime (7 ) to the corresponding ketonitrile (8 ) in one pot is reported for the first time in carbohydrate literature. Key ketonitrile intermediate (8 ) upon palladium hydroxide mediated cascade reaction afforded 1-deoxynojirimycin (DNJ)1b in moderate diastereoselectivity. The cascade reaction involves the conversion of nitrile to amine, heteroannulation, reduction of the imine and subsequent debenzylation to furnish the azasugars. This oxidative dehydration-oxidation and reductive heteroannulation methodology is successfully utilized for the total synthesis of 1-deoxynojirimycin (1b ), miglitol (2 ) and miglustat (3 ). Graphical abstract: Highlights: The polyhydroxylated heterocycles possessing an endocyclic nitrogen atom (azasugars or iminosugars), have long been an attractive synthetic target due to their unique biological properties, especially for the inhibition of a variety of sugar processing enzymes. In this manuscript a moderately yielding short synthesis of aza sugars are reported. The synthetic methodology described for azasugars here in involves a unique oxidative dehydration-oxidation of polyhydroxy-oxime (7 ) to the corresponding ketonitrile (8 ), and this unique oxidative dehydration-oxidation is reported for the first time in carbohydrate literature. The ketonitrile(8) obtained by oxidative dehydration-oxidation of hydroxy-oxime(7) on palladium hydroxide mediated cascade reaction afforded the 1-deoxynojirimycin (DNJ)1b in moderate diastereoselectivity. The cascade reaction involves the reduction of nitrile to amine, heteroannulation to imino sugar further reduction and debenzylation to azasugar in a single pot operation. This oxidative dehydration and reductive heteroannulation methodology is conveniently utilized in the total synthesis of azasugar alkaloid 1-deoxynojirimycin(1b), miglitol(2) and miglustat(3) . Thus overall strategy developed for the miglitol, miglustat, as well as deoxynojirimycin involves unique chemical transformations, which are not yet utilized in carbohydrate chemistry. This methodology utilizes simple procedures, and environmentally benign reagents and reaction conditions.